2015
DOI: 10.1038/ajg.2015.359
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Diverticula Are Not Associated With an Increased Risk of Colorectal Adenomas

Abstract: Background & Aims Patients with missed colorectal cancer have been reported to be more likely to have colonic diverticulosis. Such an association could be due to either higher risk of neoplasia or difficulty examining the colon in patients with diverticulosis. The aim of this study was to determine whether colonic diverticula are associated with an increased risk for colonic neoplasia. Methods We analyzed data from a prospective study of patients undergoing screening colonoscopy that included detailed assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…Fourteen studies were included in the meta-analysis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Figure 1 outlines the search methodology and selection process. Characteristics and quality assessment of the extracted studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies were included in the meta-analysis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Figure 1 outlines the search methodology and selection process. Characteristics and quality assessment of the extracted studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…T EN OBSERVATIONAL STUDIES (eight cross-sectional studies, [19][20][21][23][24][25][26][27] one case-control study 18 and one cohort study 22 ) involving 9633 participants were included in the data analysis for the risk of colorectal adenomas. Pooled OR of colorectal adenomas in individuals with colonic diverticula was 1.67 (95% CI 1.…”
Section: Diverticular Disease and Colorectal Adenomasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published prospective study from the United States investigating 624 participants undergoing first-time screening colonoscopy found no association between diverticula and adenomas or advanced adenomas irrespective of a proximal or distal localization and the number of adenomas, respectively [12]. Another recent retrospective study from the Netherlands reported lower detection rates in colon segments (rectosigmoid colon, descending colon, ascending colon) with diverticula, whereas overall detection rates of adenomatous polyps were similar between individuals with and without diverticulosis [15].…”
Section: Discussionmentioning
confidence: 98%
“…Peery et al . examined the effect of colonic diverticula on colonic neoplasia in 624 first‐time participants, aged ≥30 years, by a follow‐up study.…”
mentioning
confidence: 99%